Interactions between attributions and beliefs at trial-by-trial level: Evidence from a novel computer game task - Zamfir, Elena; Dayan, Peter (PLOS Computational Biology, 2022)
Author summary As part of interpreting our experiences, we spontaneously make causal attributions and use them to update our beliefs about the world, ourselves and others. This has long been a topic of interest, particularly within psychiatry. Some theories assume that people have stable “attributional styles”, others focus on the changing nature of attribution-making and on the relationships between attributions and one’s beliefs about the self, suggesting that the two are mutually connected. In this area of research, people have traditionally been asked to imagine themselves experiencing various significant life events and report on how they would interpret those, or have been exposed to artificial and highly simplified situations in the lab. In this work, we introduce a new task to study relationships between causal attributions and beliefs: repeatedly playing an engaging and relatively complex game of skill. We show that we can detect mutual influences between attributions and beliefs at the level of individual wins and losses. This has implications for how everyday successes and failures impact our beliefs about ourselves and our well-being. It also could help understand how our interpretations of negative experiences can spiral out of control, affecting our mental health.